Strategic corporate communication in the digital age - Camilleri, Mark Anthony, 1976- (Emerald Publishing Limited, 2021)
Strategic Corporate Communication in the Digital Age explores how contemporary communication approaches are crossing boundaries as innovative media formats and digital transformations offer new challenges and opportunities to academia and practitioners. New technologies have empowered various organisations and their stakeholders. The digital and social media are central to the process of building trust, reputation and support, as online users can use them to scrutinise and influence corporate decisions and actions. This authoritative book features a broad spectrum of theoretical and empirical chapters on topics relating to organisations' interactive engagement with stakeholders during COVID-19. It sheds light on dialogic communications through different digital media, the utilisation of mobile learning technologies for corporate training and development, corporate disclosures of CSR practices, communications of small and medium sized businesses, and provides a taxonomy of online marketing methods, among other topics. This title is a premier reference source and a valuable teaching resource for courses in marketing, communications, strategy and organisational behaviour.- Resumé vydavatel
Includes index.
Keywords: digitální přenosové systémy; strategický management; komunikace (sdělování); digital communications; strategic planning; human communication; elektronické knihy; sborníky; electronic books; papers of several authors